Lexical access patterns of second language speakers of English - Rasyiqah Batrisya Md Zolkapli; Khazriyati Salehuddin (Penerbit Universiti Kebangsaan Malaysia, 2019)
Vocabulary plays a major role in concept formation, acculturation, articulation, and all aspects of learning. Unfortunately, although learners may have internalized complex vocabulary through formal learning, they may not have the ability to retrieve known words and concepts or have access to the right words, or lexical access, effectively. This study explores the lexical access patterns of second language speakers of English (ESL). Fifty students from the Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, participated in this research. Twenty-five represented the more proficient ESL speakers whereas the other 25 represented the less proficient ESL speakers. Four pieces of paper, each with a high-frequency word (i.e., “man”, “people”, “time”, “day”) printed at the centre of the paper, were distributed to the participants as stimuli for them to create four sets of semantic maps. This paper thus presents a qualitative analysis of the semantic mapping of the word “man” and results show that English language proficiency does affect the way participants activate the words from their mental lexicon. The frequency of the words that were activated from the word “man” in the participants’ environment also affects the mapping. The semantic maps produced by the participants reflect ESL speakers’ pattern of lexical access, particularly in the manner the words are categorised in their mental lexicon. This study proposes that semantic mapping activity can be used to reflect and analyse ESL speakers’ vocabulary development, as well as to reflect ESL speakers’ weaknesses in accessing words and their thought patterns in the English language.